A-08 Differences in Long-term Stability of Baseline ImPACT Scores in High School Football Players. (13th July 2022) - Burley, C; Datoc, A; Lashley, L
Abstract: Purpose: To explore the long-term stability of ImPACT baseline composite scores at a one-year interval across multiple age groups within a sample of high school football players. Methods: A total of 660 high school football players completed two ImPACT baseline assessments approximately 1 year apart (average days between = 337.8, SD = 68.0). Subjects were separated into three groups based on age at first baseline: Age 14: n = 249; Age 15: n = 246; Age 16: n = 165. Subjects reporting concussion history and/or history of Learning Disability or Attention-Deficit/Hyperactivity Disorder at either timepoint were excluded. Results: Repeated measures t-tests for subjects who completed initial baseline at 14 indicated significant differences in Verbal Memory (t(248) = −2.99, p = 0.003; Cohen's d = 19), Visual Memory (t(248) = −4.47, p < 0.001; d = 0.28), and Visual Motor Speed (t(248) = −8.18, p < 0.001; d = 0.52). Repeated measures t-tests for subjects who completed initial baseline at 15 indicated significant differences in Visual Memory (t(245) = −4.82, p < 0.001; d = 0.31) and Visual Motor Speed (t(245) = −7.89, p < 0.001; d = 0.50). Repeated measures t-tests for subjects who completed initial baseline at 16 indicated significant differences in Visual Motor Speed (t(164) = −5.32, p < 0.001; d = 0.41). Conclusions: Overall, ImPACT composite scores appear more variable for younger athletes with stability increasing as athletes develop. Clinicians should consider differing degrees of variability when planning pre-season baselines (i.e., whether to assess annually or bi-annually) as well as recency of baselines when interpreting change following injury.